If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -6x + -4 = -46 + 3x + -15 Reorder the terms: 6 + -4 + -6x = -46 + 3x + -15 Combine like terms: 6 + -4 = 2 2 + -6x = -46 + 3x + -15 Reorder the terms: 2 + -6x = -46 + -15 + 3x Combine like terms: -46 + -15 = -61 2 + -6x = -61 + 3x Solving 2 + -6x = -61 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + -6x + -3x = -61 + 3x + -3x Combine like terms: -6x + -3x = -9x 2 + -9x = -61 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + -9x = -61 + 0 2 + -9x = -61 Add '-2' to each side of the equation. 2 + -2 + -9x = -61 + -2 Combine like terms: 2 + -2 = 0 0 + -9x = -61 + -2 -9x = -61 + -2 Combine like terms: -61 + -2 = -63 -9x = -63 Divide each side by '-9'. x = 7 Simplifying x = 7
| 4(5x-6)=10x+12x-2x | | 8x+5=4(3x-2)-3 | | 21+1.5h=28-2h | | x^2-3xy+2y^2-y+x=0 | | 11-(2x+5)=-5x+7 | | x/3-1/2=1/2 | | 3+2(5x-4)=3(2x-3)+2x | | 13k+5=k-11 | | (33x)+(145y)=44000 | | (145x)+(33y)=44000 | | 7(3x-8)=5(4x-11) | | e/3=15 | | 36x^2+36x+9= | | 2m=16 | | 3x-5+x=8x+7 | | 1.3x=-7 | | (6x+19)-(14x+5)= | | .3x=-7 | | 17=4x+1-2x | | -n=30 | | 4x+22=22 | | (6x+14)-(9x+5)= | | 3,75100,000= | | y^2-12y+12=0 | | 13=9x+5-5x | | 2a+6+5a=3a-10 | | -12+.2x-.3x+x=6x | | d^5+5d-4=0 | | 6x^2=x+40 | | 2g-16=-8 | | 5x+12=7x-13 | | y^2-12y+62=0 |